Sensitization of ZnO nanoparticle by vitamin B12: Investigation of microstructure, FTIR and optical properties. (December 2016) - Gharagozlou, Mehrnaz; Naghibi, Sanaz
Graphical abstract: Highlights: The sensitization of the as-synthesized ZnO NPs was conducted by loading vitamin B12 . The as-synthesized VB12 –ZnO conjugate contains about 26 wt.% of VB12 . FTIR detected a new bond at 756 cm −1, related to the out-of-plan CH bending vibration. Conjugation of ZnO to VB12 leads to appear a peak at 454 nm in the UV–vis spectrum. The modification process leads to increase PL intensity and shift toward visible region. Abstract: Vitamin B12 (VB12 ) as a biomolecule was successfully applied to modify the as-synthesized ZnO nanoparticles (NPs). VB12 –ZnO conjugate was fabricated by a solution based method, the phase component of which was independent of the modification process, as shown by X-ray diffraction (XRD) analysis. The amount of loaded VB12 on ZnO NPs was measured by thermal gravimetry (TGA) to be ∼ 25 wt.%. Fourier transform infrared (FTIR) spectroscopy was used to probe the interaction of ZnO NPs with VB12 . Although the sensitization process did not cause the appearance of any intense new peak in the FTIR results, the traces of a new band at 756 cm −1 and also the intensification of the peak at 3411 cm −1 (in comparison to ZnO spectrum) confirmed the formation of some new bands between NPs and VB12 molecules. The UV–vis spectroscopy revealed that VB12 –ZnO conjugate absorbed light irradiation at around 272, 380 and 454 nm. The third one is situated in the visible light region, originating from the conjugation between ZnO NPs and the functional ring of VB12 . The photoluminescence (PL) behavior was affected by the sensitization process, shifting the PL peak of ZnO NPs toward a higher wavelength and increasing its intensity.